Determinants of Maritime Transport Costs - Alejandro Micco; Natalia Perez (Inter-American Development Bank, Research Department, 2002)
Recent literature has emphasized the importance of transport costs and infrastructure in explaining trade, access to markets, and increases in per capita income. For most Latin American countries, transport costs are a greater barrier to U. S. markets than import tariffs. We investigate the determinants of shipping costs to the U. S. with a large database of more than 300,000 observations per year on shipments of products at the six-digit HS level from different ports around the world. Distance and containerization matter. In addition, we find that efficiency of ports is an important determinant of shipping costs. Improving port efficiency from the 25th to the 75th percentile reduces shipping costs by 12 percent. (Bad ports are equivalent to being 60 percent farther away from markets for the average country. ) Inefficient ports also increase handling costs, which are one of the components of shipping costs. We try to explain variations in port efficiency and find that they are linked to excessive regulation, the prevalence of organized crime, and the general condition of the countrys infrastructure. Finally, we present a number of success stories in Latin America to show that private involvement in port management leads to efficiency and lower costs whenever it is accompanied by labor reform, and when monopoly power is reduced through either regulation or competition.
Keywords: 330